CD56 is Expressed in Uterine Smooth Muscle Tumors. (July 2021) - Karpathiou, Georgia; Chauleur, Celine; Papoudou-Bai, Alexandra; Dagher, Sami; Peoc'h, Michel
Abstract : CD56 is used in gynecologic pathology, typically in the context of a neuroendocrine, sex cord or sex cord–like tumor. It has never been studied in uterine smooth muscle tumors, which can potentially enter their differential diagnosis, and thus CD56 positivity could potentially be a pitfall. Thus, the aim of this study was to explore its expression in this category of tumors. Seventy-eight uterine smooth muscle tumors, including 14 leiomyosarcomas, 46 leiomyomas and their variants, 14 smooth muscle tumors of uncertain malignant potential, and 4 intravenous leiomyomatoses were studied in regard to CD56 expression. Fifty-eight nearby myometria were also analyzed. Sixty-five (83.4%) tumors showed CD56 expression. Nearby myometrium showed CD56 expression in 15 cases (25.9%). Staining ranged from 10% to 100% of tumor or myometrial cells (median 80% and 50%, respectively). Among the tumor types, leiomyoma with bizarre nuclei, had the lowest extensive expression ( P =0.01). Most uterine smooth muscle neoplasms express CD56; thus, it is not useful in attempting to discriminate from endometrial stromal or sex cord–like neoplasms.